Joint effects of polycyclic aromatic hydrocarbons, smoking, and XPC polymorphisms on damage in exon 2 of KRAS gene among young coke oven workers - Chen, Siqin; Yin, Xingyue; He, Yuefeng; He, Qinghua; Li, Xiaomei; Yan, Maosheng; Huang, Suli; Lu, Jiachun; Yang, Binyao (Frontiers in Public Health, 2022)
Genetic polymorphisms may contribute to individual susceptibility to DNA damage induced by environmental exposure. In this study, we evaluate the effects of co-exposure to PAHs, smoking and XPC polymorphisms, alone or combined, on damage in exons. A total of 288 healthy male coke oven workers were enrolled into this study, and urinary 1-hydroxypyrene (1-OH-Pyr) was detected. Base modification in exons of KRAS and BRAF gene, and polymorphisms of XPC were determined in plasma by real-time PCR. We observed 1-OH-Pyr was positively related to damage in exon 2 of KRAS (KRAS-2) and in exon 15 of BRAF (BRAF-15), respectively, and KRAS-2 and BRAF-15 were significantly associated with increased 1-OH-Pyr. A stratified analysis found 1-OH-Pyr was significantly associated with KRAS-2 in both smokers and non-smokers, while 1-OH-Pyr was significantly associated with BRAF-15 only in smokers. Additionally, individuals carrying both rs2228001 G-allele (GG+GT) and rs3731055 GG homozygote (GG) genotype appeared to have more significant effect on KRAS-2. The high levels of 1-OH-Pyr were associated with KRAS-2 only in rs2228001 GG+GT genotype carriers and the high levels of 1-OH-Pyr were associated with KRAS-2 only in rs3731055 GG genotype carriers and the most severe KRAS-2 was observed among subjects carrying all four of the above risk factors. Our findings indicated the co-exposure effect of PAHs and smoking could increase the risk of KRAS-2 by a mechanism partly involving XPC polymorphisms.